A study of critical success factors and prioritization by using analysis hierarchy process in lean manufacturing implementation for Thai SMEs - Kiatcharoenpol, T.; Laosirihongthong, T.; Chaiyawong, P.; Glincha-Em, C. (My University, 2014)
This study identifies and prioritizes critical success factors (CSF) based on the implementation of Lean Manufacturing for Thai SMEs. After review of International research papers, 12 CSFs were selected and categorized into four resource types from the lens of Resource-Based View (RBV) Theory. These are Organizational, Technology, Human and Financial Resources. Interviews and surveys with Lean experts experienced in SME consultation were carried out to answer the proposed research questions. Analytical Hierarchy Process (AHP) is then applied to prioritize the relative importance of the CSFs. The results show that "Technology resource" is the most important to enhance implementation of Lean in SME organizations. This indicates the knowledge of production technology is a prime key to support process improvement according to Lean methodology. This study contributes to the existing body of knowledge by evaluating and prioritizing CSFs reflecting by grounded theory and expected outcomes at firm level from experts' experience.
Keywords: Analytical Hierarchy Process (AHP); Lean Manufacturing; Resource-Based View